A track record on SHOX: from basic research to complex models and therapy - Marchini, Antonio; Ogata, Tsutomu; Rappold, Gudrun (Endocrine reviews, 2016)
Abstract. SHOX deficiency is the most frequent genetic growth disorder associated with isolated and syndromic forms of short stature. Caused by mutations in th
Gesehen am 08.11.2018